PHYTOCHEMISTRY, PROXIMATE COMPOSITION AND SOME ESSENTIALS MINERALS PRESENCE IN AQUEOUS EXTRACT OF AZANZA GARCKEANA FRUIT PULP - Hassan, M.; Aliyara, H. Y.; Nyako, H. D.; Bobbo, A. G.; Drambi, M. (FUDMA Journal of Sciences, 2026)
The research was conducted to evaluate the proximate composition and Phytochemistry of aqueous extract of Azanza garckeana fruit pulp. The qualitative and quantitative Phytochemistry was determine using standard procedures as describe by Evans and Trease and proximate composition was determine using Association of Analytical Chemist procedures. The result of phytochemical screening of aqueous extract of Azanza garckeana fruit pulp revealed the presence of Alkaloids, Saponins, Tannins, flavonoids, while terpenoids and steroids were absent. Saponins of 3.16%. Alkaloids revealed a value of 2.51% Tannins 1.27% while Terpenoids and Steroids were absent both qualitatively and quantitatively; the following anti nutrients were present: Phenols (4.81%), Glycosides (0.41%) and Flavonoids (1.18%) respectively. The proximate composition revealed 2.67± 0.45 Moisture, 3.86± 0.12 Ash, 7.21± 0.56 Crude fibre, 9.29± 0.18 Crude Protein and 71.71± 0.68 Carbohydrate. However, essential minerals result shows Potassium having the highest value of mean plus standard error mean of 56.10 ± 0.09 followed by Sodium 20.10 ± 0.64, Magnesium 8.84 ± 0.02, Zinc 7.58 ± 0.14, and the least is Iron having 5.11 ± 0.01 and Calcium was absent. In conclusion the pulp Revealed the presence of secondary metabolites, proximate composition and some essential minerals will have a numerous applications Particularly in the Feed mill pharmaceutical industry.
Keywords: Aqueous; Extract; Composition; Proximate; Pulp; Phytochemistry